Upaya Meningkatkan Hasil Belajar melalui Penggunaan Model Project Based Lerning (PjBL) pada Mata Pelajaran Matematika Kelas IV - Ilham Panji Akbar; Sulistyowati Sulistyowati; Istiyati Mahmudah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Students' learning outcomes can be actively involved in mathematics learning activities through the application of the PjBL model. This PTK method is carried out in two cycles, each of which includes four stages, namely: planning, action implementation, observation, and reflection. This study involved 22 students from class IV B as research subjects atMIS Darul Ulum Palangka Raya, data obtained through observation techniques, tests, and documentation. The findings obtained by observation of the teacher's skills in managing the class in cycle I were recorded at 86.53% in the good category. In cycle II, the percentage increased to 92.30% in the very good category. While in cycle I, student learning activities were recorded at 71.59% in the sufficient category, but increased in cycle II with a percentage of 86.37% in the very good category. Students' posttest scores after the implementation of the PjBL learning model in cycle I showed a completeness rate of 45.45%. Meanwhile, in cycle II, there was a significant increase, through completeness reaching 90.91%. In cycle I, the increase in student learning achievement was classified as moderate, from the N-Gain score of 0.3433. In cycle II, the N-Gain score increased to 0.7314 in the high category. Based on these data, it can be concluded that the application of the PjBL model in mathematics is proven to be effective in improving the achievement of student learning outcomes.